The Correlation between Happiness and Spiritual Health with Academic Self-Efficacy among Medical Sciences Students - Amiri 1, Mohammad; Chaman 2, Reza; Mohammadnejad 3, Fahimeh; Khosravi 4*, Ahmad (Shahroud Journal of Medical Sciences, 2018)
Background: Successful accomplishment of a task or an assignment needs academic self-efficacy. This study was designed to examine the relationship between happiness and spiritual well-being with academic self-efficacy among the students of Shahrud University of Medical Sciences.Methods: We randomly selected 500 students in this cross-sectional study by employing spiritual well-being, happiness, and academic self-efficacy questionnaires in 2018. We applied the SPSS 16 software to analyze the collected data using ANOVA, Chi-square, and Pearson Correlation tests. The significance level was considered 0.05 in all tests.Results: The mean scores obtained for spiritual health and happiness were at a moderate level, accounting for 89.56±16.11 and 39.95±12.52, respectively, while the academic self-efficacy mean score was assessed to be high and equal to 109.32±18.44. We found a significant relationship between spiritual well-being and happiness with academic self-efficacy (P=0.001). The variables of happiness and gender appeared to be significant in the logistic regression final model. According to the results, women had a potential to show higher self-efficacy 1.8 times more than men. In addition, the rate of self-efficacy increased by 5% per every 1 score increase in happiness (OR=1.05).Conclusions: Due to the fact most of students showed a moderate level of spiritual health and happiness and over a third of students had a moderate level of academic self-efficacy, we need to further focus on spiritual health and happiness. Obviously, improving these two factors will be a key in improving the academic self-efficacy.